Skalenübergreifende Modellierung und Optimierung vom atomistischen kristallinen Phasenfeldmodell bis zur mesoskopischen Phasenfeldmethode - Berghoff, Marco (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2015)
Expansion of the phase field crystal model for multi-component mixtures, as ternary dendritic and lamellar eutectic crystallization. Comparison of crystal growth with molecular dynamics and phase field simulations. Parameters and initial data structures are used to simulate, starting from a small atom cluster to a ternary dendrites with side arms. Optimization techniques to reduce the amount of computation are developed.